A new species of Longtania Ding from China and redescription of the male genitalia of Platytibia ferruginea Ding (Hemiptera: Fulgoromorpha: Delphacidae) - Qin, Dao-Zheng; Zhang, Ya-Lin (Zootaxa, 2009)
A new species of the planthopper genus Longtania Ding (Hemiptera: Fulgoromorpha: Delphacidae), L. arcuata n. sp. (central southern China: Hubei) is described and illustrated. A revised diagnosis of Longtania and a key to known species is provided. The genus is tentatively placed in the subtribe Delphacina. The genus Platytibia is reviewed and is assigned to the subtribe Numatina sensu Emeljanov. The male genitalia of the type species, P. ferruginea Ding is redescribed and illustrated.